INFLAMMATORY BOWEL DISEASE - Mahaprani Danastri, I Gusti Ayu; Darma Putra, Ida Bagus (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana, 2013)
Crohn disease (CD) and ulcerative colitis (UC) is an chronic inflammation in the gastrointestinal tract. Colecctively, they are called inflammatory bowel disease (IBD), and about 1,5 millions people in America suffering from UC and CD. The cause of UC and CD is unknown, but the expert believe that UC and CD are caused by a disturbed immune response in someone who has a genetic predisposition. UC and CD have a significant recurrency  and remission rate. Surgery in UC is a curative treatment for colon’s disease and a potentially colon’s malignancy, but it is not a curative treatment for CD.
Keywords: crohn disease, ulcerative colitis, inflammatory bowel disease